Comprehensive systematic review and meta-analysis on the therapeutic efficacy of curcumin in osteoporosis: unveiling mechanisms and preclinical evidence - Yang, Sheng-lei; Wang, Jing-xiang; Ma, Fei-er; He, Jiang-hua; Zhang, Ao; Sun, Xiao-ming; Wei, Ying; Wang, Yan (Frontiers in Nutrition, 2025)
BackgroundOsteoporosis (OP) is a common degenerative bone disease that seriously affects the quality of life of patients and poses a significant public health burden. Curcumin (CUR), a natural compound, has attracted much attention due to its anti-inflammatory, antioxidant and bone protective effects. However, there is currently a lack of systematic evaluation of the efficacy and mechanism of CUR in treating OP.MethodsThis study is a systematic review and meta-analysis conducted per PRISMA guidelines. Studies meeting the inclusion criteria were retrieved and screened from the PubMed, Embase, Web of Science, and Cochrane Library databases. The included studies were limited to animal models of OP, and the intervention group was treated with a single dose of CUR. A meta-analysis was performed using Review Manager 5.4 and R Studio software. The standardized mean difference (SMD) and 95% confidence interval (CI) were calculated using the fixed-effect or random-effects model. Sources of heterogeneity, sensitivity, and publication bias were also explored.ResultsA total of 17 high-quality studies involving 282 animals were included. The results of the metaanalysis showed that compared with the control group, CUR significantly increased bone mineral density (BMD of the femur: SMD = 2.18, 95% CI: 1.53–2.83; BMD of the tibia: SMD = 1.08, 95% CI: 0.30–1.87), improved the trabecular microstructure (BV/TV: SMD = 2.74, 95% CI: 1.84–3.64; Tb.N: SMD = 2.31, 95% CI: 1.65–2.96; Tb.Th: SMD = 2.09, 95% CI: 1.43–2.76; Tb.Sp: SMD = −2.32, 95% CI: −3.15 to −1.50). In addition, CUR significantly reduced serum CTX-1 and TRAP-5b levels, while increasing OCN and ALP levels. Mechanism studies have shown that CUR may act through OPG/RANKL, Wnt/β-catenin, NF-κB, MAPK, and TGF-β/Smad2/3 signaling pathways.ConclusionThis study is the first to systematically evaluate CUR's therapeutic effect on an OP animal model. The results show that CUR can significantly improve the pathological state of osteoporosis through a multi-target mechanism and has good therapeutic potential. However, heterogeneity and differences in the quality of the literature suggest that high-quality prospective studies are needed to verify the clinical value of CUR further.